دراسة إمكانيات وضع موديل تشخيصي (مرحلة التلقين) لاهتزازات المحركات في السفينة - شلوف, محمد (Latakia University Journal -Engineering Sciences Series, 2017)
قمنا في هذه الدراسة بوضع نموذج رياضي شكَّل أساساً لوضع نموذج رقمي تشخيصي لمسألة العلاقة بين عزم دوران المحرك (وبالتالي الاستطاعة)، والخلوصات في المضجعين الأساسي والثانوي لعمود المرفق، وذلك لتشخيص قيم الخلوصات في هذه المضاجع /والتي تؤثر حتماً على العزم وعلى اهتزازات المحرك/ حيث أجريت تجارب متعددة وكبيرة الحجم لمختلف الحالات من خلال إجراء المحاكاة والتجريب الحسابي على النموذج التشخيصي، والذي يشكل المرحلة الأولى والأساسية (مرحلة التلقين) لعملية التشخيص الكاملة، وفي النهاية قمنا بمناقشة النتائج ووضعنا بعض الاستنتاجات والتوصيات لاستكمال العمل في المستقبل.In this study, we have developed a mathematical model, which formed the basis for the development of a digital diagnostic model, for the question of the relation between the engine torque (and therefore power), and the clearances in the basic and secondary bearings of the crankshaft, to diagnose clearance values in these bearings, /which will inevitably affect on the torque and the vibrations of the engine/, where multiple and various grand-scale case experiments were carried out through simulation and arithmetic experimentation on a diagnostic model, which constituted the first and main phase (the instruction phase) of the full diagnosis. And at the end we discussed the results and put some conclusions and recommendations to complete the work in the future.